2017
DOI: 10.1038/s41598-017-07912-3
|View full text |Cite
|
Sign up to set email alerts
|

Dead-end complex, lipid interactions and catalytic mechanism of microsomal glutathione transferase 1, an electron crystallography and mutagenesis investigation

Abstract: Microsomal glutathione transferase 1 (MGST1) is a detoxification enzyme belonging to the Membrane Associated Proteins in Eicosanoid and Glutathione Metabolism (MAPEG) superfamily. Here we have used electron crystallography of two-dimensional crystals in order to determine an atomic model of rat MGST1 in a lipid environment. The model comprises 123 of the 155 amino acid residues, two structured phospholipid molecules, two aliphatic chains and one glutathione (GSH) molecule. The functional unit is a homotrimer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…The GSH at full occupancy observed in the holo complex adopts a “crescent”-shaped binding mode (Fig. 2a ), similar to what has been reported for LTC 4 synthase 10 , 11 and mPGES-1 12 , while contrasting to the extended conformation described for MGST1 17 , 18 . In comparison, the GSH at partial occupancy displays several distinct features.…”
Section: Resultssupporting
confidence: 80%
“…The GSH at full occupancy observed in the holo complex adopts a “crescent”-shaped binding mode (Fig. 2a ), similar to what has been reported for LTC 4 synthase 10 , 11 and mPGES-1 12 , while contrasting to the extended conformation described for MGST1 17 , 18 . In comparison, the GSH at partial occupancy displays several distinct features.…”
Section: Resultssupporting
confidence: 80%
“…Electrospray mass spectrometric data obtained by Ålander et al (Ålander et al 2009b) showed, as also indicated by electron crystallographic data (Holm et al 2006;Kuang et al 2017), that each rMGST1 trimer binds three GSH molecules, rather than one as reported earlier (Sun and Morgenstern 1997;Lengqvist et al 2004). Equilibrium dialysis studies revealed that there is one high-affinity and two low-affinity sites for GSH and that only the high-affinity site is catalytically competent (Ålander et al 2009b); hence, MGST1 shows one-third-of-sites-reactivity.…”
Section: Structure and Propertiesmentioning
confidence: 57%
“…Cryoelectron microscopic studies provided additional details about the structure of rat MGST1 (Kuang et al 2017). rMGST1 is present as a dimer of trimers with phospholipids at the interface between the two trimers.…”
Section: Structure and Propertiesmentioning
confidence: 99%
“…The isoforms ( NM_001005957 , termed MGST1a; and NM_001002215 , termed MGST1b) are located on chromosome 4 and share ~ 56% identity at the amino acid level with the human homologue. Residues critical for activity [30] are conserved between fish and human (see Fig. S4 ) indicating similar functions.…”
Section: Resultsmentioning
confidence: 96%